Microbiological and Clinical Aspects of Actinomyces Infections: What Have We Learned? - Edit Urbán; Márió Gajdács (MDPI AG, 2021)
Obligate anaerobic bacteria are important members of the normal human microbiota, present in high numbers on mucosal surfaces (e [...]